PERBEDAAN PROFITABILITAS DAN TINGKAT PENGAWASAN SEBELUM DAN SESUDAH MERGER PADA BANK PERKREDITAN RAKYAT - I Nyoman Nugraha Ardana Putra (Jurnal Keuangan dan Perbankan, 2013)
This research was aimed at finding the influence of merger. Furthermore, it was also to find out the differenceof before and after merger to Profitability and Controlling in Society Credit Bank (BPR). In order to find outit, it included 46 Society Credit Bank (BPR-LKP) doing merger in West Nusa Tenggara province as thesample. By using t-test paired, then it came the finding that there was difference of before and after merger toprofitability in Society Credit Bank (BPR-LKP) compared with ROA indicator. Further more, it was also tofind out the difference of before and after merger to Society Credit Bank (BPR-LKP) controlled with NPLindicator.